Poken Bante: a Tradition of the Mandailing Community in Welcoming Eid Al-Fitr - Batubara, Muhammad Zusanri; Fila, Dhita Larci De (Analisa: Journal of Social Science and Religion, 2023)
The Poken Bante is a Mandailing community tradition in welcoming Eid al-Fitr. This tradition is carried out on the last day of Ramadan. This study aims to examine the activities of Mandailing people in the Poken Bante tradition, to understand the relevance of the Poken Bante tradition and Islamic teachings, and to analyze the meaning and value of the Poken Bante tradition in welcoming Eid al-Fitr. This tradition was studied using qualitative research with an ethnographic approach. The primary data was obtained through participant observation and in-depth interviews. Ethnographic notes are essential in primary data collection. Secondary data was obtained through articles, books, and archives. Data analysis in this research is ethnographic analysis by systematically examining the data obtained, the relationship between the data, and the overall relationship of the data. This research took place for one month, starting from the middle of Ramadan to Syawal in 1444 H (April - May 2023 M), located in Panyabungan District, Mandailing Natal Regency. This research found that the Poken Bante tradition is a meat market activity that arises on the last day of Ramadan due to the high demand for meat needs from the Mandailing community. The relevance of this tradition and Islam is reflected in the integration of Mandailing culture and Islamic teachings based on the Mandailing philosophy of Hombar do Adat dohot Ibadat. The meaning and value of the Poken Bante tradition are togetherness, unity, integrity, and helping.